Xi Jinping a study in power - Brown, Kerry (London Icon Books, 2022)
Although Xi Jinping came to power a decade ago, he remains an enigmatic figure in the West. His priority has always been to keep Chinese society as stable as possible, steering a course through a period of astounding economic growth, while ensuring that nothing challenges the political status quo.
Includes index
Keywords: Xi Jiping